Bridging the theory and practice of eliciting the voices of young children: findings from the Look Who's Talking project. Issue 1 (2nd January 2022) - Cassidy, Claire; Wall, Kate; Robinson, Carol; Arnott, Lorna; Beaton, Mhairi; Hall, Elaine
ABSTRACT: To foster children and young people's skills, dispositions and understanding that underpin a voice agenda, practices need to be developed that support this from the earliest age. This article explores issues relating to this complex, challenging and under-researched area from the perspective of practitioners working with children aged from birth to seven. Using vignettes of practice, we explore practical and pedagogical examples and take the opportunity to deepen our understanding of the elicitation of voice through the lens of the eight factors previously identified in the Look Who's Talking Project. Through this approach we highlight practices that elicit voice as a key element of children's rights in a localised way, and exemplify productive connections between theory and practice.